DAVID GOUVERNEUR - Planning and Design for Future Informal Settlements: Shaping the Self-Constructed City. (2015) - García García, Miriam (ZARCH, 2015)
DAVID GOUVERNEUR Planning and Design for Future Informal Settlements: Shaping the Self-Constructed City Routledge, London and New York, 2015